Synthesis of clonality and polyploidy in vertebrate animals by hybridization between two sexual species - Choleva, Lukáš; Janko, Karel; De Gelas, Koen; Bohlen, Jörg; Šlechtová, Věra; Rábová, Marie; Ráb, Petr (Evolution; international journal of organic evolution, 2012)
Because most clonal vertebrates have hybrid genomic constitutions, tight linkages are assumed among hybridization, clonality, and polyploidy. However, predictions about how these processes mechanistically relate during the switch from sexual to clonal reproduction have not been validated. Therefore, we performed a crossing experiment to test the hypothesis that interspecific hybridization per se initiated clonal diploid and triploid spined loaches (Cobitis) and their gynogenetic reproduction. We reared two F1 families resulting from the crossing of 14 pairs of two sexual species, and found their diploid hybrid constitution and a 1:1 sex ratio. While males were infertile, females produced unreduced nonrecombinant eggs (100%). Synthetic triploid females and males (96.3%) resulted in each of nine backcrossed families from eggs of synthesized diploid F1s fertilized by haploid sperm from sexual males. Five individuals (3.7%) from one backcross family were genetically identical to the somatic cells of the mother and originated via gynogenesis; the sperm of the sexual male only triggered clonal development of the egg. Our reconstruction of the evolutionary route from sexuality to clonality and polyploidy in these fish shows that clonality and gynogenesis may have been directly triggered by interspecific hybridization and that polyploidy is a consequence, not a cause, of clonality.
Keywords: rybí proteiny; polymerázová řetězová reakce; Male; Reproduction, Asexual; Česká republika; Reproduction; Sequence Analysis, DNA; sekvenční analýza DNA; Fish Proteins; molekulární sekvence - údaje; biologická evoluce; mužské pohlaví; nepohlavní rozmnožování; rozmnožování; Cypriniformes; Czech Republic; Germany; Animals; Slovenia; ženské pohlaví; Biological Evolution; zvířata; Německo; Hybridization, Genetic; Slovinsko; máloostní; Molecular Sequence Data; Polymerase Chain Reaction; hybridizace genetická; Polyploidy; Female; polyploidie